Improvements in self-compassion after an online program for adults with celiac disease: Findings from the POWER-C study. Issue 2 (17th February 2023) - Dowd, A. Justine; Tang, Karen T. Y.; Chen, Michelle Y.; Jung, Mary E.; Mosewich, Amber; Welstead, Lori; Culos-Reed, S. Nicole
ABSTRACT: Part 1 involved pilot testing two programs for people with celiac disease (self-regulation, SR; or SR plus self-compassion, SR+SC). Results from focus groups revealed participants wanted more and tailored content, and new content bi-weekly versus weekly. In Part 2, we assessed the feasibility of delivering the programs online and the effects of the programs on behavioural and psychological outcomes. All participants reported significant improvements on adherence to a gluten-free diet, quality of life, self-regulatory efficacy (SRE) and concurrent SRE. The SR+SC group reported significant improvements in self-compassion and medium effect size reductions in anxiety and depression. Findings from this study can be used to inform guidelines for strategies to help people to effectively manage and cope with celiac disease.